2017
DOI: 10.1002/jcp.26029
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles as new tools for inhibition of cancer angiogenesis

Abstract: Angiogenesis is known as one of the hallmarks of cancer. Multiple lines evidence indicated that vascular endothelium growth factor (VEGF) is a key player in the progression of angiogenesis and exerts its functions via interaction with tyrosine kinase receptors (TKRs). These receptors could trigger a variety of cascades that lead to the supply of oxygen and nutrients to tumor cells and survival of these cells. With respect to pivotal role of angiogenesis in the tumor growth and survival, finding new therapeutic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
87
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 157 publications
(89 citation statements)
references
References 106 publications
(122 reference statements)
0
87
0
Order By: Relevance
“…There are many conditions that promote angiogenesis, such as hypoxia. Under hypoxia condition, hypoxia‐inducible factor‐1 (HIF‐1) increases the expression of angiogenesis growth factors, including vascular endothelial growth factor (VEGF) and its receptors (VEGFRs; Hashemi Goradel et al, ). Consistent with this proposal, Mendes et al () reported that infection of epithelial cells with F. nucleatum increases angiogenesis via upregulating VEGF and VEGFR1 and 2.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…There are many conditions that promote angiogenesis, such as hypoxia. Under hypoxia condition, hypoxia‐inducible factor‐1 (HIF‐1) increases the expression of angiogenesis growth factors, including vascular endothelial growth factor (VEGF) and its receptors (VEGFRs; Hashemi Goradel et al, ). Consistent with this proposal, Mendes et al () reported that infection of epithelial cells with F. nucleatum increases angiogenesis via upregulating VEGF and VEGFR1 and 2.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…MiRNAs are known as small non‐coding RNAs which have central roles in vital physiological events such as apoptosis, angiogenesis, growth, and differentiation (Gholamin et al, ; Goradel et al, ; Hashemi Goradel et al, ; Reza Mirzaei et al, ; Salarinia et al, ). Hence, deregulation of these molecules could lead to activation/inhibition various molecular and cellular targets which could contribute to initiation and progression of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs are a group of noncoding RNAs, which act epigenetic players. Given that these molecules can affect a wide range of biological processes, such as growth, angiogenesis, differentiation, metastasis, and differentiation of stem cells . Given that deregulation of miRNAs are related with initiation and progression of a large number of diseases, such as cancer, diabetes, stroke, cardiovascular diseases, viral infections, and degenerative diseases .…”
Section: Mirna and Response To Therapy In Leukemiamentioning
confidence: 99%